FORMATION OF COMMUNICATION SKILLS AND INTERACTION IN UNIVERSITY STUDENTS (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines the effectiveness of communication skills and the interaction between the physical therapist and the patient as a key outcome of rehabilitation services. In particular, it analyzes the approaches to developing communication skills in higher education students, which include a combination of verbal and non-verbal communication. The features of communicative competence necessary for the professional activities of future specialists in the field of physical rehabilitation are defined.The purpose of the article is to substantiate the approaches to developing communication skills in university students, which is important for their further professional practice. The importance of mastering communication skills as a significant element of the interaction of physical (ergotherapy) therapists is emphasized, creating an atmosphere of trust and respect in which patients can actively participate in their recovery.The article examines in detail the components of verbal and non-verbal communication, their significance in the process of therapist-patient interaction. For example, verbal communication includes not just the transmission of information, but also the ability to listen, support the patient, and build trust. Non-verbal signals such as facial expressions, gestures, and tone of voice also play an important role in the perception of information and emotional support for patients.The advantages of communication skills in the planning process of rehabilitation are substantiated, enabling the identification of step-by-step goals and the achievement of effective results. It has been established that a comprehensive approach to developing communication skills can significantly enhance the rehabilitation process for patients, promoting their active participation in the treatment process.Thus, the article underscores the necessity of integrating communication skills into educational programs for students preparing to work in the field of physical rehabilitation to improve the quality of medical service delivery.
Keywords: communication; interaction; skills; students